2002
DOI: 10.1055/s-2002-36345
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroisotanshinone I Protects Against Menadione-Induced Toxicity in a Primary Culture of Rat Hepatocytes

Abstract: Dihydroisotanshinone I is a phenanthrenequinone derivative isolated from the roots of Salvia trijuga Diels. The present study demonstrated the hepatoprotective effect of dihydroisotanshinone I against menadione-induced cytotoxicity in a primary culture of rat hepatocytes. Pretreating the cells with dihydroisotanshinone I at concentrations ranging from 2.5 microM to 20 microM for 24 hours caused dose-dependent protection against hepatotoxicity induced by menadione. Intracellular glutathione level and activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Specifically, T1 has inhibited the growth of leukemia and lung and colorectal cancer cells in vitro [2931], T2A has inhibited the growth of breast cancer, glioma, leukemia, and hepatocellular carcinoma cells in vitro [3235], and CT inhibited the growth of hepatocarcinoma cells in vitro [36]. Moreover, DT, which contains an abietane-type diterpene quinone (Supplementary Figure 1A), has a protective effect against menadione-induced hepatotoxicity because of its antioxidant properties and its ability to inhibit lipid peroxidation [37]. However, the clinical effects of danshen and the underlying mechanisms of DT on prostate cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, T1 has inhibited the growth of leukemia and lung and colorectal cancer cells in vitro [2931], T2A has inhibited the growth of breast cancer, glioma, leukemia, and hepatocellular carcinoma cells in vitro [3235], and CT inhibited the growth of hepatocarcinoma cells in vitro [36]. Moreover, DT, which contains an abietane-type diterpene quinone (Supplementary Figure 1A), has a protective effect against menadione-induced hepatotoxicity because of its antioxidant properties and its ability to inhibit lipid peroxidation [37]. However, the clinical effects of danshen and the underlying mechanisms of DT on prostate cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Salvia miltiorrhiza has been widely used in traditional Chinese medicine and possess diverse pharmacological activities and therapeutic potential (XD et al, 2019;He et al, 2024). Research studies have demonstrated that DTIDTI exhibits anti-oxidant (Ip et al, 2002), and anti-cancer properties (Wu et al, 2017;Lin et al, Frontiers in Pharmacology frontiersin.org 2019). Wu (Wu et al, 2021)have shown that DTI inhibits the growth of A549 cells and H460 cells via inducing ferroptosis.…”
Section: Dihydroisotanshinone Imentioning
confidence: 99%